ANALISIS DIMENSI MUTASI JABATAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KUBU RAYA - Udin Rinaldi; Ana Yuliana; Martono Martono (Jurnal Ekonomi Integra, 2023)
ABSTRACTThe goal of this study is to examine how job transfers are affected in part and simultaneously by markers of appropriate knowledge, abilities, and attitudes. Multiple linear regression test used in a qualitative descriptive technique (standardized). The job change is the dependent variable, and the appropriateness of knowledge, abilities, and attitudes is the independent variable. sources of information from surveys and interviews. 33 employees made up the sample population (census research) used. According to the study's findings, job transfers had a big impact at the same time. Research is not fully supported by knowledge that is appropriate, and other factors have a good impact. Although the administrative skills indication is still not at its best, the skill suitability variable is good. Although the loyalty indicator is improving, the attitude appropriateness characteristic is still subpar. Logical or intellectual, psychological, and social forces on collective goals are all tied to internal restraints. Position changes may be made for reasons such as switching between career phases, enhancing people capabilities, or meeting objectives, in which case the agency will unilaterally disregard any objections.